Sensitivity and specificity of the lipoarabinomannan test compared to GeneXpert in urine samples for tuberculosis diagnosis - Irawan, Danni; Rismiarti, Zuri; Tantan, Acep; Merdekawati, Fusvita (Current Biomedicine, 2025)
Background Mycobacterium tuberculosis (MTB) is the causative agent of tuberculosis (TB), primarily affecting lung tissue but also capable of infecting pleura, lymph nodes, bones, and other extrapulmonary sites. Lipoarabinomannan (LAM) is a critical lipopolysaccharide in the outer wall of mycobacterial cells and can be detected in the urine of TB patients as an antigen. Objective This study aimed to assess the sensitivity and specificity of the LAM test compared to GeneXpert in urine samples from suspected TB patients. Methods A quasi-experimental design was employed, where urine samples were collected from patients diagnosed with TB at Sidawangi Lung Hospital, West Java Province. The LAM test was performed on 40 samples by applying 60 µL of urine onto LAM test strips, while MTB presence in urine was examined using GeneXpert. Results LAM test results showed 32.5% positivity, while 67.5% were negative. GeneXpert results indicated 20% positivity and 80% negativity. The LAM test demonstrated a sensitivity of 100% and specificity of 79.4% compared to GeneXpert, with an area under the curve (AUC) value of 0.897. Conclusion The LAM test showed high sensitivity and moderate specificity compared to GeneXpert in urine samples of suspected TB patients.